Social Integration as Mediator and Age as Moderator in Social Capital Affecting Mental Health of Internal Migrant Workers: A Multi-Group Structural Equation Modeling Approach - Zhou, Jingjing; Zhou, Jianfang; Zhang, Hongyang; Zhang, Junwei (Frontiers in Public Health, 2022)
The rise of migrant workers has been a unique social phenomenon as China goes through industrialization, urbanization, and modernization. They are a special social group formed during the economic and social transition of the country. Migration of rural labor has pushed China on its new path toward industrialization and urbanization. Because of the urban-rural dual system of the country, however, it is difficult for migrant workers to be fully integrated into host cities, making them susceptible to negative emotions and mental health issues. Therefore, their mental health is an issue of great volume in the domains of social undertakings, people's livelihood, and public health. However, existing studies have paid limited attention to the psychological profile of migrant workers and even less to the interplays among their social capital, social integration, and mental health. Targeting China's internal migrant workers, this article tapped the interactions among their social integration, social capital, and mental health with a sample of the cross-sectional data from the China Labor Dynamics Survey (CLDS) in 2018. Multi-group structural equation modeling (SEM) was employed to test the moderating action of age by analyzing whether the mediation model differed significantly in the paths among young, middle-aged, and older migrant workers. The SEM based on bootstrapping suggested that, after controlling for the influence of gender, education, marital status, personal annual income, employer type, and self-rated health, migrant workers' social capital positively affect their mental health in a significant way, with social integration playing a mediating role. In terms of age difference, middle-aged migrant workers were more subject to the aforementioned mechanism than young ones, and young migrant workers were more affected by the mechanism than older ones. This study revealed different psycho-social interplays among social capital, social integration, and mental health across young, middle-aged, and elderly migrant workers. The findings could serve as an important theoretical reference and as practical guidance for improving policies concerning migrant workers' mental health and social benefits in the context of economic transition.